Epigenetic clocks moderate the impact of marital status transitions on health in older adults - Meng-Jung Lin (PLoS ONE, 2026)
Chronological age is commonly used to study aging, but biological aging may more accurately reflect cumulative life experiences and psychosocial stressors. This study examines whether epigenetic clocks function as markers of resilience by assessing how marital status transitions are associated with biological aging and health outcomes in later life. Using data from 1,654 non-Hispanic White participants in the Health and Retirement Study, we analyzed thirteen epigenetic clocks derived from DNA methylation profiles. Ordinary least squares and Cox regression models assessed the associations between marital transitions, depressive symptoms, and mortality, adjusting for genetic and social factors. Interaction terms tested whether epigenetic clocks moderated these associations. Results showed limited associations between marital status and epigenetic clocks. Marital status changes were associated with increased depressive symptoms, but were not statistically significantly associated with mortality risk. In the full sample, interactions between epigenetic clocks and marital status change were not statistically significant for depressive symptoms, although a buffering interaction was observed for the Garagnani clock among men. For mortality, significant moderation was observed for the Hannum, Garagnani, and GrimAge clocks, with moderating patterns concentrated among men. Overall, these interaction results suggest that biologically older individuals, particularly men, exhibited greater resilience to these transitions. These findings raise the possibility that epigenetic clocks reflect accumulated life experiences and psychosocial adaptation, potentially including elements of resilience in older adults.